2022
DOI: 10.3389/fimmu.2022.1019201
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteome responses in zebrafish following λ-carrageenan-Induced inflammation are mediated by PMN leukocytes and correlate highly with their human counterparts

Abstract: Regulation of inflammation is a critical process for maintaining physiological homeostasis. The λ-carrageenan (λ-CGN) is a mucopolysaccharide extracted from the cell wall of red algae (Chondrus crispus) capable of inducing acute intestinal inflammation, which is translated into the production of acute phase reactants secreted into the blood circulation. However, the associated mechanisms in vertebrates are not well understood. Here, we investigated the crucial factors behind the inflammatory milieu of λ-CGN-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…The zebrafish model has been considered for studying the complement system since some of the components involved in the activity and regulation of the pathways of this system have been identified and cloned, including the proteins C1q [ 51 ], C4 [ 52 ], factor B [ 53 ], C3 [ 54 ], MBL [ 55 ], factor H [ 56 ], properdin [ 57 ] and CD59 [ 58 ]. Other regulatory factors of the complement system have been observed in studies on the induction of inflammatory responses in zebrafish [ 59 ]. Furthermore, high-resolution genome mapping and comparisons with the human genome have shown that the human genome has a similarity of approximately 70% with orthologous genes of zebrafish, thus emphasizing the biological reliability of this model [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish model has been considered for studying the complement system since some of the components involved in the activity and regulation of the pathways of this system have been identified and cloned, including the proteins C1q [ 51 ], C4 [ 52 ], factor B [ 53 ], C3 [ 54 ], MBL [ 55 ], factor H [ 56 ], properdin [ 57 ] and CD59 [ 58 ]. Other regulatory factors of the complement system have been observed in studies on the induction of inflammatory responses in zebrafish [ 59 ]. Furthermore, high-resolution genome mapping and comparisons with the human genome have shown that the human genome has a similarity of approximately 70% with orthologous genes of zebrafish, thus emphasizing the biological reliability of this model [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins are the main components of the physiological and metabolic pathways, and the establishment of protein-protein interaction networks and proteome profiling allows the identification of new biomarkers, disease related pathways and pathological processes. Changes in blood plasma proteome have been investigated in Atlantic salmon ( Salmo salar ) [ 13 ] and zebrafish [ 18 ], but data on changes in the proteome of intestinal tissues following dietary challenge are scarce. Kiron, Kathiresan [ 19 ] investigated alterations in the intestine mucus proteome induced by a functional diet containing a feed additive (nucleotides, antioxidant, vitamins C and E, beta-glucan) in Atlantic Salmon.…”
Section: Introductionmentioning
confidence: 99%